Tổng hợp chọn lọc lập thể tubuphenylalanine axit (Tup) của tubulysin - Hải, Lê Văn; Anh, Trần Tuấn; Lộc, Trần Văn; Chiến, Trần Văn (Vietnam Journal of Chemistry, 2017)
A highly stereoselective synthesis of tubuphenylalanine fragment (9) of tubulysin is described with the key step of Wittig condensation reaction and stereoselective hydrogenation of double bond. The desired product was confirmed by 1D and 2D-NMR spectroscopies. Keywords. Wittig reaction, triethyl-2-phosphonopropionate, phenylalanine.